″Ways to improve distant methods of work on professional agitation″ - Yaschun, T.; Gromov, E.; Fomina, N. (Problems of Engineer-Pedagogical Education, 2018)
One of the important activities of any graduating department is the development and improvement of promotional career-oriented materials. The preparation of promotional materials at the Department of Information Computer and Polygraphy Technologies of Ukrainian Engineering Pedagogical Academy was started in parallel with the opening of a computer specialty in 2001. Since then, promotional materials have gone a long way from knowledge-intensive prospectuses containing only the conceptual provisions of the training of specialists to bright illustrated leaflets, booklets, posters and advertising presentations. However, existing presentations have a standard structure and familiar text support, which, unfortunately, does not attract future entrants. In order to improve the vocational guidance process, the authors have developed an original multimedia presentation with the authors’ own poetical accompaniment. In the conducted research the existing means of presenting profession-oriented advertising information and advertising materials are analyzed; graphical material was developed, systematized, and embedded into an electronic presentation; original poetical texts were written to accompany the graphic material and included in the presentation. The developed presentation is implemented in the process of work on professional agitation during the Open Doors Day and other professional agitation meetings, published on the video hosting platform YouTube. Due to the easily accessible advertising presentation, all enrollees can familiarize themselves with the conditions of training for the specialty «Vocational Education. Computer Technologies» in Ukrainian Engineering Pedagogical Academy and make their career choice. At the same time, the professional agitation process takes place without the superfluous time spent by the university teachers, the number of views being automatically calculated. The authors believe that this development is topical, perspective and contributes to the increase in the quality of work on professional agitation.